Synergy of Islamic Religious Education in Increasing Literacy and Access to Sharia Finance - Popi Puadah; Dudi Akasyah; Hardjadinata Hardjadinata; Deden Edi; Hanifah Musa Fathullah Harun (Jurnal Iqra': Kajian Ilmu Pendidikan)
The synergy between Islamic Religious Education (PAI) and Islamic finance is a strategic urgency in answering the challenges of financial literacy of Muslims in the modern era. Islamic Religious Education not only aims to form morals and religious understanding alone, but also has great potential in building economic awareness based on Islamic values. More than 50% of students do not understand the principles of Islamic economics, this picture is obtained from the results of the final semester exam, so a deep understanding synergy is needed in this regard. This study aims to examine the synergy between Islamic Religious Education (PAI) and increasing literacy and access to Islamic finance for students majoring in economics at STIE Kusuma Negara. The background of this study is the low understanding of students regarding the principles of Islamic finance, even though they come from economics study programs. Islamic Religious Education is considered to have a strategic role in forming religious awareness and sustainable Islamic economic attitudes. Using a descriptive qualitative approach and case study method, data were collected through interviews, observations, and documentation. The results of the study indicate that the integration of Islamic finance material in the PAI curriculum and a contextual learning approach that emphasizes Islamic practices and values ​​can increase student literacy towards the concept of Islamic finance. With a success rate of learning outcomes reaching 95%, this approach has proven effective while offering an educational model that is adaptive to the development of the times and the needs of contemporary Muslim society